2022
DOI: 10.3389/fphar.2022.1012063
|View full text |Cite
|
Sign up to set email alerts
|

Nontargeted metabolomics study and pharmacodynamic evaluation of bidirectional fermentation for Ganoderma lucidum with Marsdenia tenacissima

Abstract: Lung cancer is one of the malignant tumors with the fastest incidence rate and mortality growth and the greatest threat to human health and life. Marsdenia tenacissima is an antitumor of Chinese medicine. However, Marsdenia tenacissima has low bioavailability in the human body and most of its main active substances are aglycones, such as Tenacigenin A, Tenacigenin B. This study aims to produce biotransformation products rich in pungent saponins by using Marsdenia tenacissima as a fermentation medium of Ganoder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Riboflavin, also known as vitamin B2, plays a crucial role in energy metabolism and acts as an antioxidant [ 19 ], immune function regulator, and nervous system and skin health regulator. Flavin mononucleotide (FMN) was significantly upregulated during the growth of G. lucidum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Riboflavin, also known as vitamin B2, plays a crucial role in energy metabolism and acts as an antioxidant [ 19 ], immune function regulator, and nervous system and skin health regulator. Flavin mononucleotide (FMN) was significantly upregulated during the growth of G. lucidum .…”
Section: Discussionmentioning
confidence: 99%
“…Flavin mononucleotide (FMN) was significantly upregulated during the growth of G. lucidum . FMN is a coenzyme [ 19 ]. Flavin adenine dinucleotide (FAD) and riboflavin (vitamin B2) are crucial components of biological oxidation processes, such as respiration.…”
Section: Discussionmentioning
confidence: 99%
“…A computer-aided drug design approach can be used to gain an in-depth and systematic understanding of the effectiveness and functions of the ingredients in traditional Chinese medicines ( Man and Sai, 2022 ). Previous studies have reported the various pharmacological effects of VO, including regulating lipid metabolism, scavenging free radicals, inhibiting inflammation, and preventing tumors ( Li et al., 2022 ). Therefore, in the present study, we comprehensively and systematically predicted the herb–ingredient–target and gene–pathway interactions for VO against AS using a computer-aided drug design approach involving network pharmacology, molecular docking, and MDS.…”
Section: Discussionmentioning
confidence: 99%
“…This process provides nutrients for bacteria and simultaneously alters the Chinese medicinal base material through the fungal enzyme system, resulting in complex bacteria with specific pharmacological activities, such as anti-inflammatory and antitumor activity. Li et al [ 23 ] utilized biphasic fermentation technology to biotransform Marsdenia tenacissima (MT) with Ganoderma lucidum , identifying polysaccharides, saponins, organic acid alkaloids, and flavonoids of Ganoderma lucidum co-fermentation of MT by non-targeted metabolomics analysis and stoichiometric analysis. The study revealed a significant increase in amino acids and organic acids among the 249 annotated metabolites.…”
Section: Introductionmentioning
confidence: 99%